2021
DOI: 10.1038/s41598-021-89362-6
|View full text |Cite
|
Sign up to set email alerts
|

Plantar mechanical stimulation attenuates protein synthesis decline in disused skeletal muscle via modulation of nitric oxide level

Abstract: Both research conducted under microgravity conditions and ground-based space analog studies have shown that air pump-based plantar mechanical stimulation (PMS) of cutaneous mechanoreceptors of the sole of the foot is able to increase neuromuscular activity in the musculature of the lower limbs. This type of stimulation is able to attenuate unloading-induced skeletal muscle atrophy and impaired muscle function. The aim of the present study was to evaluate the effects of PMS on anabolic signaling pathways in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 82 publications
4
21
0
Order By: Relevance
“…42,43 In addition, this process depended on the level of nitric oxide in the soleus muscle. 43 The above studies support the idea that PMS can be involved in the regulation of myosin phenotype transformation and protein metabolism in rat postural muscle under unloading conditions. Thus, evidence suggests that the stimulation of the cutaneous mechanoreceptors of the feet during unloading conditions may help to preserve some cytoskeletal proteins and thereby intrinsic stiffness of soleus muscle fibers.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 In addition, this process depended on the level of nitric oxide in the soleus muscle. 43 The above studies support the idea that PMS can be involved in the regulation of myosin phenotype transformation and protein metabolism in rat postural muscle under unloading conditions. Thus, evidence suggests that the stimulation of the cutaneous mechanoreceptors of the feet during unloading conditions may help to preserve some cytoskeletal proteins and thereby intrinsic stiffness of soleus muscle fibers.…”
Section: Introductionmentioning
confidence: 99%
“…As early as at the 1st day of the hindlimb unloading of rodents, a significant decrease in the level of protein synthesis was observed in the soleus muscle [ 83 ]; at the same time, there was not yet any significant decrease in muscle mass observed. A reduced level of protein synthesis, determined using the SuNSET method, was also observed at later stages of hindlimb unloading (3rd, 7th, 14th days) [ 83 , 84 , 85 ]. A decrease in the level of protein synthesis assessed using radioactive labeling was observed after 3-, 4-, 7- and 28-day or hindlimb unloading of rodents [ 86 , 87 , 88 , 89 ].…”
Section: Molecular Signaling Alterations In Skeletal Muscles Under Disuse Conditionsmentioning
confidence: 99%
“…Recent studies in our laboratory showed that nitric oxide plays an important role in the regulation of protein synthesis and GSK-3 activity, as well as the content of ribosomal RNA at later stages of hindlimb unloading (day 7) [ 85 ]. Mechanical stimulation of the feet support zones prevented a decrease in the content of 18S and 28S rRNA after 7 days of hindlimb unloading in rats due to nitric oxide production.…”
Section: Molecular Signaling Alterations In Skeletal Muscles Under Disuse Conditionsmentioning
confidence: 99%
See 2 more Smart Citations